If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.18(y + -6) + 0.12y = 0.04y + -0.03(10) Reorder the terms: 0.18(-6 + y) + 0.12y = 0.04y + -0.03(10) (-6 * 0.18 + y * 0.18) + 0.12y = 0.04y + -0.03(10) (-1.08 + 0.18y) + 0.12y = 0.04y + -0.03(10) Combine like terms: 0.18y + 0.12y = 0.3y -1.08 + 0.3y = 0.04y + -0.03(10) Multiply -0.03 * 10 -1.08 + 0.3y = 0.04y + -0.3 Reorder the terms: -1.08 + 0.3y = -0.3 + 0.04y Solving -1.08 + 0.3y = -0.3 + 0.04y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-0.04y' to each side of the equation. -1.08 + 0.3y + -0.04y = -0.3 + 0.04y + -0.04y Combine like terms: 0.3y + -0.04y = 0.26y -1.08 + 0.26y = -0.3 + 0.04y + -0.04y Combine like terms: 0.04y + -0.04y = 0.00 -1.08 + 0.26y = -0.3 + 0.00 -1.08 + 0.26y = -0.3 Add '1.08' to each side of the equation. -1.08 + 1.08 + 0.26y = -0.3 + 1.08 Combine like terms: -1.08 + 1.08 = 0.00 0.00 + 0.26y = -0.3 + 1.08 0.26y = -0.3 + 1.08 Combine like terms: -0.3 + 1.08 = 0.78 0.26y = 0.78 Divide each side by '0.26'. y = 3 Simplifying y = 3
| x-43=-37 | | 2x+1=-2 | | 5x+10=120-8x | | 3+x+4x=48 | | x+3.2=9.3 | | 4x^3+9x^2-2x+2=0 | | 6=-2x+6x-2 | | 5x-2=x+16# | | 2x+1/12-3x-5/12=5/12 | | 6-7x+6x=2 | | Z^2+3x=10 | | x+3.6=9.7 | | 4=z/9.1 | | 8(c+1)=2(c-2) | | -8=14+x | | 5(3x+9)-5= | | 10+7x+3x=50 | | 2x+39=11+9x | | 75=7x+x+3 | | x^2-2x-130=0 | | 30x^2+51x+9=0 | | 60=8(3+b)/2 | | -46=-2x-3x-6 | | 4+4x=16+4x | | -4+3x+6x=41 | | 6x-8y=-4 | | 75=0.2*x | | 2x^2-3x+18=0 | | 5+9i/1+i | | z/3-8=14 | | 56x-14/24x-6 | | x+2x+x=y |